STUDI PERBANDINGAN PRODUK INSEKTISIDA FORMULASI EC (EMULSIFIABLE CONCENTRATE) DENGAN PENAMBAHAN SURFAKTAN DIETANOLAMIDA MENGGUNAKAN VORTEX, MIXER DAN HOMOGENIZER - Muh Agus Ferdian ,Erliza Hambali, dan Mulyorini Rahayuningsih (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Insecticide formulations form EC (emulsifiable concentrate) required the selection of an effective instrument if would be adopted by an industry. The selection is associated with long process of using energy and equipment investment. The aim of this study was to determine the type of homogenization equipment that effective to formulate emulsion of EC insecticide. Buprofezin was used as the active ingredient insecticide formulations. Solvesso 150 as solvent, surfactant diethanolamide (DEA) and water using three types of homogenization tools vortex, mixer and homogenizer. The results showed the use of homogenizer was more effective than the other equipment insectcide parameters generated from the homogenizer were: density of 0.9681 ± 0.002 g/cm3; droplet size of 3,961 ± 0.092 µm; surface tension of 25.695 ± 0.808 dyne/cm; contact angle of 30.213 ± 0.237° and viscosity of 4.673 ± 0.164 cP.Keywords: buprofezin,diethanolamide, EC formulation, insecticide